Improving the charge carrier separation efficiency at the perovskite/carbon electrode interface in HTL-free carbon-based perovskite solar cells via physical polishing. (25th May 2023) - Zhao, Zeren; Wu, Yulin; Wu, Shan; Li, Chao; Ma, Fangyuan; Ma, Mengmeng; Tang, Xuan; Wang, Jinyao; Zhou, Liya; He, Xipu; Wang, Zhijie; Liu, Kong; et al.
Abstract: Carbon-based perovskite solar cells (C-PSCs) are favored by researchers for their low cost and support for large-scale production. However, the particles precipitated on the surface of the perovskite (PVK) film can affect the fabrication and operation of C-PSC, such as disrupting the coating of C electrode film and producing defects that can aggravate the carrier recombination. Herein a reliable and efficient C-PSC is prepared by applying a physical polishing strategy. The compact interface contact and the larger Fermi level difference at the carbon-PVK (C/PVK) interface are achieved, resulting in a 21.4% increase in power conversion efficiency compared to that without polishing. A hole-transport-layer-free C-PSC with an efficiency of 12.2% is achieved, resulting from the reduction of PVK surface roughness and defects that cause non-radiative recombination. It is revealed that the physical polishing can reduce the root mean square roughness from 15.9 nm to 1.2 nm, facilitating the screen printing of the C electrode. The carrier lifetime of the PVK film also increases from 39.9 ns to 73.3 ns, which improves the photocurrent of the solar cell. We believe that the improved C/PVK interface contact will provide a solid foundation for the future large-scale commercial production of PSCs.